2020
DOI: 10.1039/d0nr03475d
|View full text |Cite
|
Sign up to set email alerts
|

In situ unraveling of the effect of the dynamic chemical state on selective CO2 reduction upon zinc electrocatalysts

Abstract: Unraveling the reaction mechanism behind CO2 reduction reaction (CO2RR) is a crucial step for advancing the development of efficient and selective electrocatalyst to yield valuable chemicals. To understand the mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Previously, it was reported that the products of CO 2 RR on Cu-based catalysts were relatively complex and could be affected by the surface wettability, local pH, microstructure, exposed facets, and doping, as well as the applied potentials. ,,, For comparison, the EC performance of the bare carbon paper electrode was evaluated, and the FE of H 2 was as high as 80% at all tested potentials (Figure S16). We also tested it on the metallic Cu (Figure S17) and Zn (Figure S18) electrodes, and a large FE of H 2 (>40%) was obtained at all potentials in accordance with the previously reported results. , It was much larger than the FE­(H 2 ) with the as-prepared CuZn catalysts (Figure S19). Note that the CO, C 2 H 4 , HCOO – , CH 4 , C 2 H 5 OH, and CH 3 COO – were detected for all Cu 10– x Zn x aerogels (Figure S19), consistent with the previous reports. ,,,, However, the FE of CH 4 , HCOO – , C 2 H 5 OH, and CH 3 COO – was kept nearly unchanged with the variation of Cu/Zn ratio, suggesting that chemical composition tuning had little effect on the generation of these products.…”
supporting
confidence: 90%
“…Previously, it was reported that the products of CO 2 RR on Cu-based catalysts were relatively complex and could be affected by the surface wettability, local pH, microstructure, exposed facets, and doping, as well as the applied potentials. ,,, For comparison, the EC performance of the bare carbon paper electrode was evaluated, and the FE of H 2 was as high as 80% at all tested potentials (Figure S16). We also tested it on the metallic Cu (Figure S17) and Zn (Figure S18) electrodes, and a large FE of H 2 (>40%) was obtained at all potentials in accordance with the previously reported results. , It was much larger than the FE­(H 2 ) with the as-prepared CuZn catalysts (Figure S19). Note that the CO, C 2 H 4 , HCOO – , CH 4 , C 2 H 5 OH, and CH 3 COO – were detected for all Cu 10– x Zn x aerogels (Figure S19), consistent with the previous reports. ,,,, However, the FE of CH 4 , HCOO – , C 2 H 5 OH, and CH 3 COO – was kept nearly unchanged with the variation of Cu/Zn ratio, suggesting that chemical composition tuning had little effect on the generation of these products.…”
supporting
confidence: 90%
“…3 a show that the sample with the least Zn content (1-CuZn) produced the least FE for HCOO − at 9.68%, while the sample with the highest Zn content (4-CuZn) produced the highest FE at 22.6%. Note that CO production likely takes place on the ZnO sites, while HCOO − production takes place on the reduced ZnO sites 66 , 67 . As a − 1.10 V vs. RHE potential (i.e., the reduction potential of Zn(II) at this particular pH) is applied, ZnO would always be reduced during the CO 2 RR experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hydrogen evolution, the C 1 products of CO and formate are the major products for s-ZnO, which is consistent with common ZnO nanoparticles or foil. 7 On the contrary, for s-CuO, the C 2+ products of C 2 H 4 and C 2 H 5 OH dominated the reduction current in the range of −0.71 V and −2.16 V. However, the introduction of a small amount of ZnO (s-Cu 5 Zn 1 O x ) inhibited the activity of CuO, especially for the C 2+ products. Compared with s-CuO, the total FE of the C 2+ products dropped sharply and was replaced by CO as the main product, which was similar to the CO 2 RR behavior of s-ZnO.…”
Section: Resultsmentioning
confidence: 95%
“…2–4 The electrochemical CO 2 reduction reaction (CO 2 RR) is emerging as a viable method to consume excess carbon dioxide in the atmosphere and store chemical energy in value-added chemicals. 5–7 Therefore, efforts have been devoted to exploring efficient electrocatalysts with high selectivity for the CO 2 RR because CO 2 can be converted into formate, methanol (CH 3 OH), methane (CH 4 ), ethylene (C 2 H 4 ) ethanol (C 2 H 5 OH), etc . Among these, due to its relatively clean combustion in combustion engines, 8 high energy density and suitability to the present infrastructure for natural gas storage and transport, 9,10 the product of methane has shown significant economic benefits.…”
Section: Introductionmentioning
confidence: 99%